Identification of a cytolytic protein in the coelomic fluid of Eisenia foetida earthworms - Bilej, M; Brys, L; Beschin, A; Lucas, R; Vercauteren, E; Hanusová, R; De Baetselier, P (Immunology letters, 1995)
Total coelomic fluid of earthworms Eisenia foetida (Oligochaeta, Annelida) is capable of lysing different mammalian tumor cell lines. This cytolytic activity is different from tumor necrosis factor (TNF)-mediated lysis and is not due to proteolysis. Total coelomic fluid was subjected to ion-exchange chromatography separation and a fraction with prominent cytolytic activity was used to elicit monoclonal antibodies that were screened for their capacity to neutralize the cytolytic effect of total coelomic fluid. One of the prepared neutralizing IgG antibodies was used for the immunoaffinity purification of a cytolytic factor from total coelomic fluid. SDS-PAGE and Western blot analyses revealed a protein band with an apparent molecular weight of 42 kDa. This cytolytic protein (termed CCF-1 or coelomic cytolytic factor 1) can be adsorbed on the surface of opsonized particles and may be involved in opsonizing and hemolytic effects of coelomic fluid.
Keywords: lektiny; Opsonin Proteins; Oligochaeta; tělesné tekutiny; Cross Reactions; Hemolytic Plaque Technique; Body Fluids; monoklonální protilátky; zkřížené reakce; nádory plic; Fibrosarcoma; Lung Neoplasms; ovce; Cytotoxins; Sheep; Flow Cytometry; opsoniny; chromatografie afinitní; hemolytická plaková technika; průtoková cytometrie; Animals; Carcinoma; Lectins; zvířata; fibrosarkom; karcinom; nádorové buňky kultivované; myši; Tumor Cells, Cultured; Antibodies, Monoclonal; Mice; Chromatography, Affinity; cytotoxiny